Influences of inlet height and velocity on main performances in the cyclone separator. (18th August 2019) - Zhang, Jianping; Zha, Zhenting; Che, Peng; Ding, Honglei; Pan, Weiguo
ABSTRACT: Aiming at improving collection efficiency in the cyclone separator, the effects of inlet height and velocity on tangential velocity, static pressure and collection efficiency were studied. A three-dimensional model including gas-flow, and particle-dynamics fields was built by the Reynolds stress turbulence model, and the numerical simulation was achieved using the FLUENT software. The static pressure distribution, tangential velocity distribution, and particle trajectory of the cyclone were obtained, and the variation law of the collection efficiency with inlet height and velocity as well as particle diameter was analyzed. Numerical results indicate that both the static pressure and the tangential velocity in the cyclone basically present the axial symmetrical distribution, the static pressure shows a nonlinear increasing trend in the radius direction and the distribution of the tangential velocity is in the shape of a "hump." The increase of inlet height in a certain range reduces the rotation numbers of particles in the cyclone and shortens the residence time, which results in the improvement of trapping performance. Furthermore, the appropriately increasing inlet velocity in a reasonable range can make the collection efficiency increased.